Apprenticeship skills pay off on the labor market - Christina Langer; Jakob Peiffer; Simon Wiederhold (EconPol Forum, 2023)
Apprenticeship plans provide the basis for reliably and comprehensively classifying the skills of a large share of Germany's workforce. In total, we classify more than 13,000 different skills and the duration of learning each skill based on the apprenticeship plans. Workers who have acquired higher cognitive, social, or digital skills during their apprenticeship earn higher wages in the short and long term. In particular, the value of digital skills has risen sharply since the 1990s, parallel to the increasing use of computers in the workplace. The speed at which apprenticeship plans are modernized is crucial for how well the German apprenticeship system can prepare its graduates for the future labor market.
Keywords: 330